Restorative Justice, Reconciliation, and Peacebuilding (Oxford University Press, 2014)
All over the world, the practice of peacebuilding is beset with common dilemmas: peace versus justice, religious versus secular approaches, individual versus structural justice, reconciliation versus retribution, and the harmonization of the sheer number of practices involved in repairing past harms. Progress towards resolving these dilemmas requires reforming institutions and practices but also clear thinking about basic questions: What is justice? And how is it related to the building of peace? The twin concepts of reconciliation and restorative justice, both involving the holistic restoration of right relationship, contain not only a compelling logic of justice but also great promise for resolving peacebuilding's tensions and for constructing and assessing its institutions and practices. This book furthers this potential by developing not only the core content of these concepts but also their implications for accountability, forgiveness, reparations, traditional practices, human rights, and international law.